Pengaruh Program Literasi Terhadap Minat Siswa dalam Pembelajaran Bahasa Indonesia di Kelas VIII - Hanum, Nur Kholida; Ningrum, Seftia Wulan Ayu; Saufaqillah, Iktarna Faris; Jayanti, Rani; Hidayat, Taufiq; Yahya, Yuwafa Faurelio; Aziz, M. Aqmal (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study is to understand students' interest in literacy programs that affect their learning outcomes. This study uses a quantitative approach with a survey method, and the results are expressed in a Likert scale and numerical statistics. Statistics is the data analysis technique used. This data analysis technique uses regression and descriptive statistics. The results of this study show that literacy programs have a positive impact on student learning outcomes. The percentage results show that student interest significantly affects student learning outcomes, with 13% in the high category, 40% in the very high category, 47% in the high category, and 40% in the low category. Meanwhile, in terms of student learning outcomes, 40% were in the very high category, 47% in the high category, 13% in the sufficient category, and only 0% in the low and very low categories.